Rapid-Response and Highly Sensitive Boronate Derivative-Based Fluorescence Probe for Detecting H2O2 in Living Cells - Muthusamy Selvaraj; Kanagaraj Rajalakshmi; Yun-Sik Nam; Yeonhee Lee; Byoung Chan Kim; Sung Jin Pai; Sang Soo Han; Kang-Bong Lee (Journal of Analytical Methods in Chemistry)
Intracellular H2O2 monitoring is important and has driven researchers to pursue advancements for the rapid identification of H2O2, since H2O2 is short-lived in cell lines. An arylboronate derivative has been investigated as a chemospecific fluorescence recognition agent for H2O2. Triphenylimidazoleoxadiazolephenyl (TPIOP) boronate was contrived as a novel candidate for the rapid and sensitive recognition of H2O2. The probe was conjugated using the TPIOP functional group acting as an excellent fluorescent enhancer. The TPIOP group stimulated the polarization of C–B bond due to its extended π-conjugation, which included heteroatoms, and induced the production of rapid signal because of the highly polar C–B bond along with the corresponding boronate unit. While H2O2 reacts with TPIOP boronate, its nucleophilic addition to the boron generates a charged tetrahedral boronate complex, and then the C–B bond migrates toward one of the electrophilic peroxide oxygen atoms. The resulting boronate ester is then hydrolyzed by water into a phenol, which significantly enhances fluorescence through aggregation-induced emission. The TPIOP boronate probe responded to H2O2 rapidly, within 2 min, and exhibited high sensitivity with a limit of detection of 8 nM and a 1000-fold selectivity in the presence of other reactive oxygen species. Therefore, the developed TPIOP boronate chemodosimeter was successfully utilized to visualize and quantify intracellular H2O2 from human breast cancer (MCF-7) cells, as well as gaseous and aqueous H2O2 from environmental samples using Whatman paper strips coated with TPIOP boronate.